2014
DOI: 10.14737/journal.aavs/2014/2.4.199.203
|View full text |Cite
|
Sign up to set email alerts
|

Real Time and Conventional PCR for Characterization of Salmonella sp. from Imported Meat to Egypt

Abstract: This study was aimed to detect Salmonella spp. in imported frozen beef and buffalo meat cuts from India, Brazil, Australia and Newzeland. One hundred frozen meat samples were collected from supermarkets located at Alexandria province and from Alexandria port. Salmonella was biochemically identified in 18/100 (18%) samples. Serologically, S. paratyphi A and S. typhi were detected in 10/18 (55.56%) and 8/18 (44.44%) positive samples, respectively. Using conventional PCR, 18/18 (100%) were confirmed to be pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…The colony characteristics of Salmonella spp. found in this study was translucent, black smooth, small round colonies on SS agar, pink color colony with black centre in XLD agar, were similar to the findings of other authors (Elsayed et al,2014;Harsojo and Sari, 2015;Hamad et al 2010). In Gram's staining, the morphology of the isolated Salmonella spp.…”
Section: Discussionsupporting
confidence: 93%
“…The colony characteristics of Salmonella spp. found in this study was translucent, black smooth, small round colonies on SS agar, pink color colony with black centre in XLD agar, were similar to the findings of other authors (Elsayed et al,2014;Harsojo and Sari, 2015;Hamad et al 2010). In Gram's staining, the morphology of the isolated Salmonella spp.…”
Section: Discussionsupporting
confidence: 93%
“…Higher incidences of Salmonella spp., of 80%, and 46.67%, however, were recorded in buffalo meat in Laos [ 26 ], and Bangladesh [ 27 ], respectively. Conversely, lower incidences of 7% [ 28 ], 7.11% [ 29 ], 18% [ 30 ], 10.66% [ 31 ], and 7.4% [ 32 ] were reported for Salmonella in buffalo meat samples from Iran, Laos, Egypt, India, and Nepal, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…From the result recorded in table 5 it's clear that 3 Salmonella serovars were identified in the examined frozen meat samples and identified as 2 (6.7%) strains as S. papuana, 1 (3.3%) strain as S. paratyphi A and 1 (3.3%) strain as S. vircho. Higher results were reported by Elsayed MS, et al [46] where they stated that S. paratyphi A was detected in 8/18 (44.44%) positive samples.…”
Section: Serotyping Of the Isolated Salmonellaementioning
confidence: 59%
“…Nearly similar results were recorded by El-Kader HA, et al [29] (10%), but higher results reported by AL-Jobori KM, et al [7] (40%) and Mahmood NR, et al [45] who isolated Salmonellae spp. at a rate of 24.76% and Elsayed MS, et al (18%) [46].…”
Section: Introductionmentioning
confidence: 97%